2013
DOI: 10.1042/bj20121832
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a pre-export enzyme–chaperone complex on the twin-arginine transport pathway

Abstract: The Tat (twin-arginine translocation) system is a protein targeting pathway utilized by prokaryotes and chloroplasts. Tat substrates are produced with distinctive N-terminal signal peptides and are translocated as fully folded proteins. In Escherichia coli, Tat-dependent proteins often contain redox cofactors that must be loaded before translocation. Trimethylamine N-oxide reductase (TorA) is a model bacterial Tat substrate and is a molybdenum cofactor-dependent enzyme. Co-ordination of cofactor loading and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…As such, domains II and III bind the guanine moieties of each pterin which extend close to the protein surface. At one extremity of the Moco molecule, domain IV constitutes a cap whose rotation would allow access to a wide funnel for Moco insertion as recently suggested1528. Notably, our comparative SAXS analysis of both the apoNarGH and holoNarGH revealed that cofactor-dependent conformational changes are restricted to the catalytic subunit NarG.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…As such, domains II and III bind the guanine moieties of each pterin which extend close to the protein surface. At one extremity of the Moco molecule, domain IV constitutes a cap whose rotation would allow access to a wide funnel for Moco insertion as recently suggested1528. Notably, our comparative SAXS analysis of both the apoNarGH and holoNarGH revealed that cofactor-dependent conformational changes are restricted to the catalytic subunit NarG.…”
Section: Discussionsupporting
confidence: 58%
“…Whilst preliminary, a SAXS study performed on a chaperone-molybdoenzyme complex, apoTorAD showed a largely folded catalytic subunit15. Herein, Moco is the sole prosthetic group of TorA, catalytic subunit of the trimethylamine N -oxide reductase and member of the Mo/W- bis PGD family42.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This strongly suggests that NapA is present in a more ‘open’ conformation in the complex, which would be consistent with a lack of MoCo in the NapA precursor. The shape of the complex is not dissimilar in overall architecture to the SAXS‐derived model for the TorAD complex . However, unlike the TorAD complex where the component high‐resolution structures of TorA and TorD could be well fitted into the SAXS envelope by rigid body modelling, the rigid body models created for the NapDA SAXS data had less volume than the corresponding ab initio models, even when integrating flexibility into the model by allowing flexibility in the orientation of domain IV of NapA (which is the only domain of Nap/DMSO reductase family enzymes that is formed from a contiguous stretch of polypeptide chain and which is known to be flexible in the TorA precursor ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their Tat‐targeting role, they also act as binding sites for biosynthetic chaperones . A well‐studied example of a signal‐peptide‐binding biosynthetic chaperone is TorD, which binds to the twin‐arginine signal peptide of its cognate Tat substrate trimethylamine‐ N ‐oxide reductase, TorA, and at a second site close to the mature N‐terminus . TorD binding facilitates molybdenum cofactor insertion into TorA by maintaining the apoprotein in an open conformation, simultaneously shielding the substrate from interacting with the Tat machinery while allowing the cofactor to insert.…”
Section: Introductionmentioning
confidence: 99%